Adaptation of the Robot Anxiety Scale into Turkish - (:unkn) unknown (My University, 2019)
The involvement of robots in people's lives causes concerns about how human-robot interaction canbe achieved. In this study, it is aimed to obtain the Turkish version of Robot Anxiety Scale. The dataobtained from university students were analyzed by explanatory factor analysis and confirmatoryfactor analysis. 11 items in the scale were divided into three factors. According to the confirmatoryfactor analysis, the fit index values of the model were acceptable. This study shows that the Turkishversion of the scale has discriminant validity, and the scale is a reliable and valid measurement toolthat may help to understand how effective the design and properties of robots to be used in Turkishculture.

Robotların insanların hayatında yer alması insan-robot etkileşiminin nasıl sağlanacağına dair endişelere sebep olmaktadır. Bu çalışmada ise Robot Kaygısı Ölçeğinin Türkçe versiyonunun elde edilmesi amaçlanmıştır. Üniversite öğrencilerinden elde edilen veriler açıklayıcı faktör analizi ve doğrulayıcı faktör analizi ile incelenmiştir. Ölçekte bulunan 11 madde üç faktöre bölünmüştür. Doğrulayıcı faktör analizi sonucuna göre modelin uyum indeksi değerleri kabul edilebilir seviyededir. Bu çalışma, elde edilen ölçeğin Türkçe versiyonunun ayırıcı geçerliliğe sahip olan güvenilir ve geçerli bir ölçüm aracı olmasından ve Türk kültüründe kullanılması planlanan robotların dizaynlarının ve özelliklerinin ne derece etkin olabileceğini anlamaya yardım edeceğinden dolayı önemlidir.
Robot Kaygısı Ölçeğini Türkçeye Uyarlama Çalışması